The United States and Decolonization
XVII, 247 p.
Keywords: At the international level the twentieth century was characterized by the rise in national self-determination in the Third World and by the rise of US power. This book analyzes the dynamics of the changing relationships between the United States and states seeking decolonization, within the contexts of the US relationship with the European colonial powers, the Cold War, and the economic system. Its scope is broad in both space and time. This collection of articles brings together leading scholars as well as recently qualified authors on a subject that was confined in the Cold War paradigm, but ultimately needs to transcend it.